2005
DOI: 10.1093/eurheartj/ehi556
|View full text |Cite
|
Sign up to set email alerts
|

Does implementation of the European guidelines based on the SCORE model double the number of Norwegian adults who need cardiovascular drugs for primary prevention? The Tromsø study 2001

Abstract: The implementation of the European guidelines could imply a doubling of the numbers of Norwegian adults on cardiovascular medication for primary prevention. Contributors to the increase would be more frequent drug use in men and elderly people, particularly for LLD use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 13 publications
4
42
1
2
Order By: Relevance
“…The gap between observed and guideline-recommended LLD use may reflect the fact that adherence to Framingham-based thresholds for intervention has been problematic in clinical practice. Norwegian population studies have shown that European SCORE-based guidelines classify most adults at high CVD risk with an ''unfavourable'' high cholesterol [2,5,6]. Implementation of these guidelines may lead to a marked increase in pharmacological treatment, especially in men and among the elderly [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gap between observed and guideline-recommended LLD use may reflect the fact that adherence to Framingham-based thresholds for intervention has been problematic in clinical practice. Norwegian population studies have shown that European SCORE-based guidelines classify most adults at high CVD risk with an ''unfavourable'' high cholesterol [2,5,6]. Implementation of these guidelines may lead to a marked increase in pharmacological treatment, especially in men and among the elderly [5].…”
Section: Discussionmentioning
confidence: 99%
“…Norwegian population studies have shown that European SCORE-based guidelines classify most adults at high CVD risk with an ''unfavourable'' high cholesterol [2,5,6]. Implementation of these guidelines may lead to a marked increase in pharmacological treatment, especially in men and among the elderly [5]. Hence, we would expect a continuance in regional differences in LLD sales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Norway has one of the highest predicted lifespans the findings seemed to invalidate the predictive ability and clinical performance of SCORE in this population, and issues regarding ethical dilemmas associated with risk labelling and medicalisation were also raised. [19][20][21][22] The version of SCORE used was outdated, however, and needed recalibration.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты норвежского исследования показывают, что использование европейской шкалы SCORE удвоит коли-чество лиц, нуждающихся в препаратах для первичной профилактики ССЗ [548] . В данную группу лиц будут включены мужчины и пожилые люди, которые имеют показания к приему гиполипидемических препаратов .…”
Section: причины препятствующие внедрению шкал оценки рискаunclassified